Social psychological research on gender, sexuality, and relationships: reflections on contemporary scientific and cultural challenges - Glick, Peter (Frontiers in Social Psychology, 2023)
This inaugural article considers two types of challenges -scientific and cultural -facing researchers who study gender, sexualities, and relationships. For the scientific challenges, I focus on the tension between constructing parsimonious theories while simultaneously accounting for the complexity of gender, sexuality, and relationships. I focus on ambivalent sexism theory as an example that illustrates both the advantages and disadvantages of parsimonious theories before turning to a topic for which achieving parsimony has been elusive: gender identity. Finally, I address the current, highly politicized cultural environment, addressing attempts to suppress gender and sexual diversity, as well as to silence teaching and research on these topics.